THE ELEMENTS OF MINAS ARTISANAL CHEESE PRODUCTION IN THE SERRA DA CANASTRA REGION (MG): LANDSCAPE AND TERRITORY FROM THE PERSPECTIVE OF CULTURAL GEOGRAPHY - Nascimento, Ramon Spironello do [UNESP]; Rosalin, Joao Paulo [UNESP]; Ismael, Vinicius de Paula [UNESP] (Univ Federal Mato Grosso, 2021)
This article makes a relationship between the elements used in the production of Minas artisanal cheese in the region of Serra da Canastra in Minas Gerais with their environmental conditions. These elements stand out for having an intrinsic relationship with the territory and landscape of which they are inserted, with emphasis on the morphoclimatic domain of the cerrado and its relief from the seas of hills. Thus, the theoretical-methodological framework of cultural geography becomes essential for understanding this relationship between cultural and social practices linked to the environment from which the artisanal Canastra Minas cheese is a product.
Keywords: CRAFTED MINAS CHEESE; SERRA DA CANASTRA; CULTURAL GEOGRAPHY